METHODOLOGICAL FEATURES OF STUDYING THE EFFECT OF SOIL POLLUTION BY EXOGENOUS CHEMICALS ON PUBLIC HEALTH. - Yusupkhujaeva A.M.; Kurbanova Sh.I. (Scholar Express Journals, 2023)
In the literature there is only information about chronic exposure during professional contact with pesticides (Yu. I. Kundiev et al. "Without-the danger of using pesticides"). There is no data in the literature on the chronic effects of pesticides on the health of the population in agricultural areas, taking into account the level of soil contamination with biocides.
Keywords: health; soil contamination; population